The complete chloroplast genome of pioneering plant Cyperus difformis (Cyperaceae) in ecological restoration. Issue 1 (2nd January 2019) - Zhu, Zixian
Abstract: Cyperus difformis is a pioneering plant of aquatic and moist habitats, which is widely distributed in southern Europe and plays an important role in sand fixation, soil improvement, and water purification. Here, the complete chloroplast genome of the C. difformis has been reconstructed from the whole-genome Illumina sequencing data. The circular genome is 167, 974 bp in size, and comprises a pair of inverted repeat (IR) regions of 38, 040 bp each, a large single-copy (LSC) region of 83, 484 bp and a small single-copy (SSC) region of 8, 410 bp. The total GC content is 36.1%, while the corresponding values of the LSC, SSC and IR region are 34.6%, 27.7%, and 38.6%, respectively. The chloroplast genome contains 137 genes, including 91 protein-coding genes, 8 ribosomal RNA genes, and 38 transfer RNA genes. The maximum-likelihood phylogenetic analysis showed a strong sister relationship with Carex plants in Cyperaceae. Our findings provide a foundation for further investigation of chloroplast genome evolution in C. difformis and other pioneering plants.